ΕVALUATING POPULATION HEALTH: THE SELECTION OF MAIN DIMENSIONS AND INDICATORS THROUGH A PARTICIPATORY APPROACH - Paula SANTANA; Angela FREITAS; Claudia COSTA; Artur VAZ (European Journal of Geography)
Population health is influenced by complex interactions between multiple determinants, but there are still large gaps in knowledge about how to comprehensively evaluate the impact of these factors on health. This paper presents the participatory approach used to select a comprehensive set of dimensions and indicators to integrate the Population Health Index; a holistic measure aimed to evaluate the health of the Portuguese population over the past 20 years. It considers the multiple dimensions of population health and experts’ judgements from different knowledge areas. Using a combination of Delphi method in two successive processes of consultation and nominal group review, it was reached a consensus on 62 indicators considered relevant for evaluating population health. The main dimensions were Economic and Social, Physical Environment, Healthcare Services, Lifestyles, Mortality and Morbidity. The results of the participatory approach reflects the diversity of points of view and emphasizes the holistic and multidimensional character of health.